Keseimbangan Marshallian atau Cheungian dalam sewakongsi: kajian empirik di Nepal - Mamat, Sahak; Baharumshah, Ahmad Zubaidi; Chew, Tek Ann; Acharya, Ram N. (Penerbit Universiti Kebangsaan Malaysia, 1997)
The issue of resource allocation under share tenancy system has always been a rich source of controversy in the economic literature. The Marshallians believe that the share tenants apply variable inputs less intensively than the fixed rent tenants or owner-operators, while the Cheungians argue that there would be no difference in input intensity across different tenure systems. This study examines the empirical validity of these approaches, using evidence from two tarai villages of Nepal. Using a model proposed by Shaban, the differences in input and output intensities in owner-occupied and sharecropped land were analysed. The results of this study indicate that share tenants apply variable inputs less intensively than owner-operators. This study, therefore, supports the Marshallian school in the sharecropping controversy.